DUKUNGAN ASPEK SOSIAL EKONOMI MASYARAKAT DALAM RANGKA PERENCANAAN REHABILITASI HUTAN DAN LAHAN DI SUB DAS AMANDIT, KABUPATEN HULU SUNGAI SELATAN - Asysyfa Asysyfa (Jurnal Hutan Tropis, 2011)
This study aims at identifying socio-economic support to communities throughout the forest, that it could be a reference for designers and policy makers within the forest and Land rehabilitation on the future, especially on Amandit sub watershed Hulu Sungai Selatan Regency.       The results obtained support the Social Aspects of Economic Support has a total value of 47.07, or induced factors Very Strong ownership of land, where most farmers have farms of more than 1 ha, in addition to the level of farmer adoption of soil conservation technologies are quite good.            Forests and Lands references rehabilitation for this type of closure reeds and bushes in the forest protected areas with the aim of reforestation activities carried out with priority species such as river basins, while the surface cultivated with a view to the reforestation activities carried out with the priority species of plants to increase the income of individuals.Keywords: socio-economic, land rehabilitation, watershed